THE EFFECTIVENESS OF AN EDUCATIONAL DESIGN ACCORDING TO THE (VARK) MODEL OF LEARNING STYLES IN THE ACHIEVEMENT OF STUDENTS OF THE INSTITUTE OF FINE ARTS IN ANATOMY - Zainab Hussein Shakir; AmerahKhaleelEbrahim (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Aims: The current research aims to identify: The effectiveness of an educational design according to the (VARK) model of learning styles in the achievement of students of the Institute of Fine Arts in anatomy.Sample: The researcher randomly selected the students of the sculpture branch to represent the control group in which the students study anatomy in the usual way (lecture and discussion). The students of the drawing branch chose to represent the experimental group whose students are exposed to the independent variable (instructional design according to the (VARK) model of learning styles) when teaching Anatomy.Results: The results of the research resulted in the superiority of the students of the experimental group who studied according to the educational design based on the (VARK) model of learning patterns over the students of the control group who studied according to the usual method in the collection of anatomy material, as well as the effectiveness of teaching by educational design according to the (VARK) model of patterns Learning to improve subject achievement.Conclusions: The educational design according to the (VARK) model of learning styles has proven its effectiveness in raising students' achievement (cognitive and skill) in anatomy.